Economic Growth Modeling for the Republic of Kazakhstan Based on the Higher Energy Efficiency Level - Ongdash, Ainur O.; Omirtay, Amalbek D.; Bayetova, Manshuk T.; Ongdashuly, Ernur (International Journal of Energy Economics and Policy, 2020)
The research on high energy efficiency achievement is believed to be relevant because this issue of energy policy is currently considered as one of the main tools for modernization of the industry of the Republic of Kazakhstan. Thus, in spite of the significant energy potential, Kazakhstan is much behind developed countries regarding energy efficiency values. So the goal of the research is to develop a model describing conditions how to achieve energy efficiency as a factor in the sustainable economy development in Kazakhstan. The following methods were used in the research: 1) mathematical statistics: the Pearson r-coefficient was calculated at the stage of searching the correlation between energy efficiency and GDP dynamics. The Pearson’s r was determined (-0.31) to be negative and weak, confirming the hypothesis that the energy efficiency state does not significantly affect the Kazakhstan GDP dynamics; 2) cognitive modeling: a cognitive map was developed to analyze the relationship between the energy efficiency and the economic development of Kazakhstan, to determine the economic development potential by refusing global energy efficiency projects and solving local problems related to reduced cost of energy resources instead. Keywords: energy efficiency, energy saving, resources JEL Classifications: Ðž14, D24, Ð¡41 DOI: https://doi.org/10.32479/ijeep.10523